Isolation, Virulence Genes and Antimicrobial Susceptibilities of Shiga Toxin-Producing Escherichia coli O157 from Slaughtered Cattle in Abattoirs and Ground Beef Sold in Elazig - Kalender, Hakan (Kafkas Univ, Veteriner Fakultesi Dergisi, 2013)
Shiga Toxin-Producing Escherichia coli O157 (STEC O157) is a foodborne pathogen. Contaminated meat and meat products have an important role in human STEC O157 outbreaks. The aims of this study were to investigate the presence of STEC O157 in slaughtered cattle in abattoirs and ground beef sold in Elazig, and to determine virulence genes and antimicrobial resistance patterns of STEC O157 isolates. A total of 540 rectal swab samples were collected immediately after slaughter. In addition, 100 ground beef samples were obtained from the butcher shops. Selective enrichment, immunomagnetic separation and plating on Sorbitol MacConkey Agar with cefixime and tellurite (CT-SMAC Agar) were used for the culture. Presence of genes encoding shiga toxin 1 and 2 (stx1 and stx2), H7 flagella (fliCh7), enterohemolysin (hlyA), intimin (eae) and O157 (rfbE) in the isolates was detected by Polymerase Chain Reaction (PCR). In the PCR analysis of rectal swab samples., 34 of 82 sorbitol negative isolates were positive for E. coli O157. 22 (64.7%) of E. coli O157 isolates belonged to E. coli O157: H7. STEC O157 was detected in 18 (3.3%) of rectal swab samples. STEC O157: H7 was isolated from 2 (2%) of ground beef samples. All STEC O157 isolates contained hlyA and eae genes. All STEC O157 isolates obtained from both rectal swab and ground beef samples were resistant to four or more antimicrobials. All STEC O157 isolates were resistant to penicillin, clindamycin, tiamulin and tilmicosin. Two STEC isolates were resistance to ampicillin. Six STEC O157 isolates were resistance to chlortetracycline and sulphadimethoxine. One STEC O157 isolate was resistant to enrofloxacin, florfenicol and oxytetracycline.
Elazı?'da mezbahalarda kesilen Sı?ırlardan ve piyasada satılan kıymalardan shiga toksin üreten escherichia coli o157'nin i?zolasyonu, virulens genleri ve antibiyotiklere duyarlılıkları
Keywords: E. coli O157; Cattle; Ground beef; Virulence genes; Antibiotic resistance